In quest of nitrogen use-efficient rice genotypes for drought-prone rainfed ecosystems - Karmakar, Biswajit; Haefele, Stephan M.; Henry, Amelia; Kabir, Md Humayun; Islam, Aminul; Biswas, Jatish Chandra (Frontiers Media, 2021)
Nitrogen (N) use efficiency in rainfed agriculture is generally low because of poor management and unavailability of suitable rice genotypes. There is a need to select rice genotypes with high N use efficiency for these specific environments, which was investigated at the Bangladesh Rice Research Institute, Regional Station, Rajshahi, in two successive years. The performance of six rice genotypes, IR7437170-1-1, BR7873-5*(NIL)-51-HR6, IR83377-B-B-93-3, International Rice Research Institute (IRRI) 123, IR83381-B-B-6-1, and Binadhan-7, were tested under four N rates (0, 55, 83, and 110 kg N ha−1) in a strip-plot design. Grain yields generally increased up to 83 kg N ha−1 and declined thereafter. Depending on N rates, mean grain yields increased by 35–45% compared to the control (N0). However, the grain yields of IR83377-B-B-93-3, IRRI 123, and Binadhan-7 increased up to 110 kg N ha−1. N uptake and its use efficiencies were the highest in IR83377-B-B-93-3, which was at par with those in IRRI 123. Bangladesh Rice Research Institute (BRRI) dhan56 and Binadhan-7 showed intermediate performance, while BRRI dhan57 and IR83381-B-B-6-1 showed lower N uptake and N efficiencies. Between 16.5 and 19.2 kg N uptake was required to produce 1 ton of paddy. The genotypes IR83381-B-B-93-3 and IRRI 123 were the most N use efficient irrespective of N rates, but BRRI dhan57 and IR87781-B-B-6-1 were observed to be inefficient genotypes, while BRRI dhan56 and Binadhan-7 were intermediate. Thus, this study indicates the need to test existing and new germplasm for optimal N rates and their NUE, especially in rainfed environments where optimized resource use is essential for higher yields and increased farmers' income.